2011
DOI: 10.1254/jphs.11037fp
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2–Receptor Antagonists Ameliorate Indomethacin-Induced Small Intestinal Ulceration in Mice by Activating α7 Nicotinic Acetylcholine Receptors

Abstract: Abstract.We have reported that nicotine and the specific α7AChR agonist ameliorate indomethacin-induced intestinal lesions in mice by activating α7 nicotinic acetylcholine receptors (α7nAChR). Dopamine D 2 -receptor antagonists, such as domperidone and metoclopramide, enhance the release of ACh from vagal efferent nerves. The present study examined the effects of domperidone and metoclopramide on indomethacin-induced small intestinal ulceration in mice, focusing on the α7AChR. Male C57BL/6 mice were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Other conventional prokinetic agents have also been reported to have an anti-ulcerogenic action in rat gastric mucosal injury models. In a previous study, the dopamine D 2 receptor antagonists metoclopramide and domperidone ameliorated small intestinal ulcers through cholinergic receptor stimulation followed by dopamine D 2 receptor inhibition in an indomethacin ulcer model [32]. Further studies may be required to assess the anti-ulcerogenic action of conventional prokinetic agents such as metoclopramide in dogs In this study, gastric emptying was delayed by prednisolone administration.…”
Section: Discussionmentioning
confidence: 63%
“…Other conventional prokinetic agents have also been reported to have an anti-ulcerogenic action in rat gastric mucosal injury models. In a previous study, the dopamine D 2 receptor antagonists metoclopramide and domperidone ameliorated small intestinal ulcers through cholinergic receptor stimulation followed by dopamine D 2 receptor inhibition in an indomethacin ulcer model [32]. Further studies may be required to assess the anti-ulcerogenic action of conventional prokinetic agents such as metoclopramide in dogs In this study, gastric emptying was delayed by prednisolone administration.…”
Section: Discussionmentioning
confidence: 63%
“…For example, in a mouse model of acute indomethacin-induced intestinal damage, Yasuda et al [125] found that dopamine D2 receptor antagonists reduced the severity of damage, and these effects were mediated through the activation of endogenous anti-inflammatory pathways mediated by via a7-nicotinic acetylcholine receptors, as had been observed previously [126] . Using the same model, Kato et al [127] demonstrated that certain 5-HT receptors could modulate susceptibility to NSAID-enteropathy.…”
Section: Nsaid-enteropathymentioning
confidence: 56%
“…The homogenized samples were subjected to three freeze-thaw cycles and centrifuged at 500g for 10 minutes. MPO activity in the supernatant was determined spectrophotometrically at 450 nm using o-dianisidine hydrochloride (Sigma-Aldrich, St. Louis, MO), as described previously (Yasuda et al, 2011). Sample protein content was estimated using a bicinchoninic acid spectrophotometric assay kit (Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Excised colon tissues were rinsed with cold PBS, homogenized in ice-cold Krebs-HEPES buffer (pH 7.4) containing a cocktail of protease inhibitors (Complete Mini; Roche, Mannheim, Germany), and then centrifuged at 1100g at 4°C for 15 minutes. The production of ROS (primarily superoxide) was determined via a chemiluminescence assay using L-012 (Wako) as described previously (Yasuda et al, 2011).…”
Section: Methodsmentioning
confidence: 99%